ASPEK REPRODUKSI LOBSTER (Panulirus sp.) DI PERAIRAN TELUK EKAS PULAU LOMBOK - M Junaidi; N Cokrowati; Z Abidin (Jurnal Kelautan, 2010)
Purposes of this research are to know some reproduction aspects of lobster, including sex ratio, gonad maturity level, size of first gonad mature, fekundity, and relationship of length-weight some. This research was conducted in June until November 2009 in Ekas Bay. During research 5 lobsters species were obtained, they are Panulirus homarus, P. versicolor, P. ornatus P. penicillatus and P. longiceps, with their of is well-balanced (1:1). Size of first gonad mature of P. homarus at carapace length 77,44 mm that happened during June - November with fekundity 28.000 - 96.000 granule, P. versicolor at carapace length 82,20 mm that happened during June - September with fekundity 16.500 - 71.000 granule, P. ornatus at carapace length 76,74 mm that happened during September - November with fekundity 47.000 - 87.000 granule, P. penicillatus at carapace length 69,84 mm that happened during June - November with fekundity 31.000 - 150.000 granule and P. longiceps at carapace length 68,47 mm that happened in June - August with fekundity 47.000 - 140.000 granule. Relationship of carapace length and body weight of five species, also male and female was described using linier regression equation and have negative allometrict pattern, where accretion of carapace length was quicker than body weight accretion.Keyword : reproduction aspect, lobster, Ekas Bay